The Mechanism of B.O.F. Fume Formation - Goetz, Fred (My University, 1980)
An industrial B.O.F., located at the #1 Melt Shop of Dominion Foundries and Steel Ltd., was used to develop and evaluate a method of measuring the rate of fume emissions during steelmaking.
The fume rate was observed to decrease with increasing time into the blow. Approximately 60% of the total fume iron losses are emitted during the first one-third of the blowing time. The fume rate is influenced by such process variables as: metal carbon content, slag volume, metal temperature and lance practice.
The mechanism of fume formation was assessed using the size, shape and chemical analyses of the fume material. The major mechanism is that of the explosive oxidation of metal droplets in the oxygen impact zone. Evidence of vaporization was also observed, but this represented less than 10% (by weight) of the total fume iron losses during the blowing period.
Keywords: Materials Science and Engineering; Metallurgy; Materials Science and Engineering